2009
DOI: 10.1097/qai.0b013e3181b32646
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Trajectory of HIV-Infected Children Accessing Care in Kinshasa, Democratic Republic of Congo

Abstract: Objective To assess the effect of HIV care (including HAART if eligible) on neurodevelopment. Design Prospective cohort study Methods Motor and mental development of 35 HIV-infected children (age 18-71 months) was assessed at entry into care, and after 6 and 12 months using age-appropriate tools. Developmental trajectory was compared to 35 HIV-uninfected, affected and 90 control children using linear mixed effects models. Effects of age (≤ or >29 months) and timing of entry into care (before or after HAART… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 31 publications
0
52
1
Order By: Relevance
“…The study concluded that cognitive deficits in HIV positive children potentially occur in infancy and they do not improve with initiation of ART after one year of age. However, another study of HIV-positive children aged 18 to 71 months 21 found that early initiation of primary HIV care and ART, resulted in improved motor development and possibly cognitive development. Our study supports this observation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that cognitive deficits in HIV positive children potentially occur in infancy and they do not improve with initiation of ART after one year of age. However, another study of HIV-positive children aged 18 to 71 months 21 found that early initiation of primary HIV care and ART, resulted in improved motor development and possibly cognitive development. Our study supports this observation.…”
Section: Discussionmentioning
confidence: 99%
“…This in part may be due to differences in neurodevelopmental assessment, poor ART availability and adherence, differences in populations assessed as a majority of these studies were in urban settings, as well as the lack of prospective data where confounders could potentially be controlled for. Antiretroviral Therapy (ART) improves survival of HIV-infected children, and has been shown to reduce neurologic pathology, 19;20 and HIV-infected children accessing care have improved motor development scores 21 . ART is becoming increasingly available in resource-poor settings, although little is known about the impact of age at initiation and duration of ART on neurodevelopment.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Initiating cART during the pre-school years (<6 years) also appears to positively affect neurodevelopment, since PHIV+ children ages 18-71 months with lower neurodevelopmental function relative to their HIV-exposed uninfected peers demonstrated developmental gains after one year of cART. [10] In contrast, children who initiated early cART (i.e, without clinical and/or immunological progression) later in childhood (median age 6.4 years) did not experience greater cognitive improvement compared to children who initiated cART when such progression had occurred, highlighting the importance of early cART initiation in infancy. [11] Despite the recent evidence for the benefit of early cART on neurodevelopment in early childhood, it remains unclear if this positive effect will persist through school-age years and adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few studies on the effects of ART on neurocognitive development in Sub Saharan Africa. Findings have been variable and early initiation of ART appears to be critical (Feucht, Hoehnen, Brisley, Forsyth, & Kruger, 2009;Laughton et al, 2009;Smith, Adnams, & Eley, 2008;Van Rie, Dow, Mupuala, & Stewart, 2009;Van Rie, Mupuala, & Dow, 2008;Van Rie et al, 2007). Two South African cohort studies found high pre-ART levels of neurocognitive delay with no improvement following six months of ART (Feucht et al, 2009;Smith et al, 2008).…”
mentioning
confidence: 99%